Black Campaign Absalom dalam Refleksi Kepemimpinan Kristen: Sebuah Kajian Teologis 2 Samuel 15: 1-12 - Yohana Fajar Rahayu; Yonatan Alex Arifianto (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2023)
Behavior that reasoned deceitfulness often occurs in today's leadership, using unconventional ways to rise and replace previous leadership positions. In the theological study of 2 Samuel 15: 1-12, there is a historical story about how a king's son wanted to coup his parents' leadership deceitfully, namely the black campaign. Using descriptive qualitative methods, it can be concluded that Christian leadership should answer the problem of leadership regeneration. So actions in the name of power, personal and group interests, with black campaigning behavior are not free to take advantage. Therefore, descriptive black campaigning in the frame of the Bible is a severe lesson regarding honesty and integrity of leadership, as well as being chivalrous to accept leadership calls naturally and based on the Bible. Christian leadership needs to see and study the historical story of Abslom's rebellion using the desire to rule over the kingdom with black campaign intrigue, which can be witnessed in 2 Samuel 15: 1-12. To bring out the value and essence of Christian leadership as a dedicated responsibility to be actualized. Therefore, Christian leadership reflects Absalom's leadership Against black campaigning as a theological study of equipping believers and Christian leadership to live righteously for this world.